Correlation of cholinergic abnormalities with senile plaques and mental test scores in senile dementia. Issue 6150 (25th November 1978) - Perry, E K; Tomlinson, B E; Blessed, G; Bergmann, K; Gibson, P H; Perry, R H
Abstract : Necropsy brain tissue from normal (control) patients and patients with depression and dementia was examined for activities of various cholinergic components, and these related to the degree of senile plaque formation and extent of intellectual impairment. Choline acetyltransferase and acetylcholinesterase activities decreased significantly as the mean plaque count rose, and in depressed and demented subjects the reduction in choline acetyltransferase activity correlated with the extent of intellectual impairment as measured by a memory information test; muscarinic cholinergic receptor binding activity remained unchanged with increasing senile plaque formation but butyrylcholinesterase activity increased. The results suggest a close relation between changes in the cholinergic system and Alzheimer's dementia, but the precise role of the system in this disease remains to be elucidated.